1992
DOI: 10.1128/jb.174.21.6857-6861.1992
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of phosphoenolpyruvate phosphomutase from Pseudomonas gladioli B-1

Abstract: Phosphoenolpyruvate phosphomutv-'^(PEPPM) catalyzes C-P bond formation by intramolecular rearrangement of phosphoenolpyruvate to pr fhonopyruvate (PnPy). We purified PEPPM from a gram-negative bacterium, Pseudomonas gladioli B isolated as a C-P compound producer. The equilibrium of this reaction favors the formation of the phosphate ester by deaving the C-P bond of PnPy, but the C-P bond-forming reaction is physiologically significant. The C-P bond-forming activity of PEPPM was confirmed with a purified protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 22 publications
(21 reference statements)
1
14
0
Order By: Relevance
“…1). The fosfomycin pathway PEP mutase-encoding gene from S. wedmorensis (14) has been sequenced, and the enzyme has been purified/ characterized from a probable fosfomycin-producing strain, Pseudomonas gladioli (25). The bialaphos pathway PEP mutase-encoding gene from S. hygroscopicus (24) has been sequenced, but because of its instability, the S. hygroscopicus enzyme has only been partially purified (19).…”
Section: Discussionmentioning
confidence: 99%
“…1). The fosfomycin pathway PEP mutase-encoding gene from S. wedmorensis (14) has been sequenced, and the enzyme has been purified/ characterized from a probable fosfomycin-producing strain, Pseudomonas gladioli (25). The bialaphos pathway PEP mutase-encoding gene from S. hygroscopicus (24) has been sequenced, but because of its instability, the S. hygroscopicus enzyme has only been partially purified (19).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the COP bond of phosphonopyruvate can be intramolecularly rearranged to form a phosphate ester, phosphoenolpyruvate, by the action of the enzyme phosphoenolpyruvate phosphomutase (17). However, COP bond cleavage is not the only route by which organophosphonate biodegradation may proceed with both transaminases (22) and oxidoreductases (4), acting on parts of organophosphonate molecules other than the COP bond; indeed, microorganisms that degrade organophosphonates without COP bond cleavage have been described in recent years (15,23).…”
mentioning
confidence: 99%
“…The ability of the enzyme to catalyze the intramolecular rearrangement of phosphonopyruvate to phosphoenolpyruvate was examined using the coupled ADP-pyruvate kinase-NADHlactate dehydrogenase system of Nakashita et al (17); this revealed a rate of phosphoenolpyruvate formation some 1000-fold lower than that of pyruvate and P i . Phosphoenolpyruvate did not itself serve as a substrate for phosphonopyruvate hydrolase.…”
Section: Characterization Of Phosphonopyruvate Hydrolasementioning
confidence: 99%